2016
DOI: 10.1016/j.molimm.2016.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Complement factor H modulates the activation of human neutrophil granulocytes and the generation of neutrophil extracellular traps

Abstract: Factor H (FH) is a major inhibitor of the alternative pathway of complement activation in plasma and on certain host surfaces. In addition to being a complement regulator, FH can bind to various cells via specific receptors, including binding to neutrophil granulocytes through complement receptor type 3 (CR3; CD11b/CD18), and modulate their function. The cellular roles of FH are, however, poorly understood. Because neutrophils are important innate immune cells in inflammatory processes and the host defense aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 70 publications
(122 reference statements)
3
52
0
Order By: Relevance
“…Factor H binding to neutrophils was demonstrated by Avery and Gordon in 1993, which binding was found to be specific and could be enhanced by neutrophil activation [95]. This receptor-mediated binding was confirmed by other groups and the β2 integrin CR3 was identified as the major factor H receptor [55,59,63]. While factor H can bind to CR4, as well, it is difficult to dissect CR3-and CR4-specific factor H effects on neutrophils because these cells express little amount of CR4.…”
Section: Factor H and Neutrophil Granulocytesmentioning
confidence: 81%
See 1 more Smart Citation
“…Factor H binding to neutrophils was demonstrated by Avery and Gordon in 1993, which binding was found to be specific and could be enhanced by neutrophil activation [95]. This receptor-mediated binding was confirmed by other groups and the β2 integrin CR3 was identified as the major factor H receptor [55,59,63]. While factor H can bind to CR4, as well, it is difficult to dissect CR3-and CR4-specific factor H effects on neutrophils because these cells express little amount of CR4.…”
Section: Factor H and Neutrophil Granulocytesmentioning
confidence: 81%
“…(3) Third, factor H can bind to various cells through receptors. Receptor-bound factor H could still act as cofactor for factor I and aid in cellular protection against complement attack [55]. In addition, receptor-bound factor H can mediate or regulate cellular adhesion and activation, i.e.…”
Section: Factor H Family Proteins In Their Non-canonical Role As Modumentioning
confidence: 99%
“…For example, Avery et al first identified complement receptor 3 (CR3, also known as CD11b/CD18 or integrin αMβ2) as a FH receptor on human neutrophils [99], where CR3 engagement by FH and FHL-1 modulates cell activation and function [100]; interestingly, recent data show that while FH can support neutrophil recruitment, it may also play an anti-inflammatory role, reducing tissue damage by influencing the formation of neutrophil extracellular traps [101]. Available data indicate that FH likely also binds CR4, possibly triggering a similar cellular response, e.g.…”
Section: Other Ligands Of Factor Hmentioning
confidence: 99%
“…In this non-canonical role, FH was described to act as a bridging molecule between complement receptor 3 (CR3; CD11b/CD18) and pathogens, and helping either pathogen entry into host cells or the antimicrobial response of the host cells (51, 5862). Such scenarios were described for FH bound to S. pneumoniae, N. gonorrhoeae , and Candida albicans (5861).…”
Section: Role Of Fh In Host–microbe Interactionsmentioning
confidence: 99%